1998
DOI: 10.1021/np980144f
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial and Cytotoxic Activity of Natural Bisbenzylisoquinoline Alkaloids

Abstract: As part of an ongoing collaborative effort to discover new antimalarial agents from natural sources, we have tested 53 bisbenzylisoquinoline alkaloids for cytotoxicity against cultured mammalian cells and for antiplasmodial activity against chloroquine-sensitive and chloroquine-resistant clones of Plasmodium falciparum. The isolates from Cyclea barbata, Stephania pierrei, Stephania erecta, Pachygone dasycarpa, Cyclea atjehensis, Hernandia peltata, Curare candicans, Albertisia papuana, and Berberis valdiviana e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 18 publications
2
83
0
Order By: Relevance
“…Berbamine (3), another alkaloid of the plant roots, exerts antimalarial activity against chloroquine-sensitive and -resistant strains of P. falciparum in vitro with the IC 50 values of 603 and 359 nM, respectively (Ye et al, 1993). A further study by Angerhofer et al (1999) suggested that 3 shows in vitro activity with an IC 50 value of 313 nM.…”
Section: Introductionmentioning
confidence: 99%
“…Berbamine (3), another alkaloid of the plant roots, exerts antimalarial activity against chloroquine-sensitive and -resistant strains of P. falciparum in vitro with the IC 50 values of 603 and 359 nM, respectively (Ye et al, 1993). A further study by Angerhofer et al (1999) suggested that 3 shows in vitro activity with an IC 50 value of 313 nM.…”
Section: Introductionmentioning
confidence: 99%
“…natural products. They are reported to have a variety of biological activities, including antimalarial (Frappier et al, 1996), cytotoxic (Angerhofer et al, 1999), anti-HIV (Kashiwada et al, 2005), antitumor , dopamine inhibitory (Cortes et al, 1992;Protais et al, 1995), antihypertensive (Qian, 2002), antibacterial (Lohombo-Ekomba et al, 2004), and smooth muscle relaxant activity (Zafra-Polo et al, 1993). However, 5-HT 1A receptor binding activity by bisbenzylisoquinoline alkaloids has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The drug-sensitive cell line KB3-1 has intermediate sensitivity to cytotoxic agents and is recommended for use in the evaluation of the selectivities of antiplasmodial drugs (2). IC 50 for inhibition of hypoxanthine uptake were reported previously (18,19).…”
Section: Methodsmentioning
confidence: 93%